Differential gene expression in the calvarial and cortical bone of juvenile female mice - Jerome Nicolas Janssen; Rotem Kalev-Altman; Rotem Kalev-Altman; Tali Shalit; Dalit Sela-Donenfeld; Efrat Monsonego-Ornan (Frontiers in Endocrinology, 2023)
IntroductionBoth the calvarial and the cortical bones develop through intramembranous ossification, yet they have very different structures and functions. The calvaria enables the rapid while protected growth of the brain, whereas the cortical bone takes part in locomotion. Both types of bones undergo extensive modeling during embryonic and post-natal growth, while bone remodeling is the most dominant process in adults. Their shared formation mechanism and their highly distinct functions raise the fundamental question of how similar or diverse the molecular pathways that act in each bone type are.MethodsTo answer this question, we aimed to compare the transcriptomes of calvaria and cortices from 21-day old mice by bulk RNA-Seq analysis.ResultsThe results revealed clear differences in expression levels of genes related to bone pathologies, craniosynostosis, mechanical loading and bone-relevant signaling pathways like WNT and IHH, emphasizing the functional differences between these bones. We further discussed the less expected candidate genes and gene sets in the context of bone. Finally, we compared differences between juvenile and mature bone, highlighting commonalities and dissimilarities of gene expression between calvaria and cortices during post-natal bone growth and adult bone remodeling.DiscussionAltogether, this study revealed significant differences between the transcriptome of calvaria and cortical bones in juvenile female mice, highlighting the most important pathway mediators for the development and function of two different bone types that originate both through intramembranous ossification.